If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + m = 9m + -7 Reorder the terms: 8 + m = -7 + 9m Solving 8 + m = -7 + 9m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9m' to each side of the equation. 8 + m + -9m = -7 + 9m + -9m Combine like terms: m + -9m = -8m 8 + -8m = -7 + 9m + -9m Combine like terms: 9m + -9m = 0 8 + -8m = -7 + 0 8 + -8m = -7 Add '-8' to each side of the equation. 8 + -8 + -8m = -7 + -8 Combine like terms: 8 + -8 = 0 0 + -8m = -7 + -8 -8m = -7 + -8 Combine like terms: -7 + -8 = -15 -8m = -15 Divide each side by '-8'. m = 1.875 Simplifying m = 1.875
| -z+6=-6 | | 5b+40=200b+400 | | 60-5x=22x+18 | | 2x=7y-11 | | 4x+4x=23x | | y/78+93=95 | | (7)-(14)= | | 3x+15+8=3x+15 | | 3f-8=f | | 3(2y-1)-y=2(y+2)-(y-4) | | (44-x)-2=3x-6 | | -22-6x=-9x | | -910=-26a | | 4(n-3)-2(n+2)=3(n+5)-n | | a+x=t | | x^2-4k+1=-5 | | 60=6(6-2x) | | 5x+7=3x+3 | | 11x+5=15+10x | | 3x^4=360 | | f+3=15 | | 4x+3(x-1)=-2(x-3)+9 | | 2/5(x-4)=2x | | f-3=15 | | 2f+3=15 | | 2g=60+5g | | 7x=4x+18 | | 4*.25x-2=0 | | 2f-3=15 | | -2x+1+9x-5=7x-4 | | p+9=4p-12 | | (-(x-4)(x-4))=0 |